Peranan Al-Qur’an terhadap Pemikiran dan Dinamika Sekularisme - Lazuardy Azra; Gea Pramudyah; Imam Abdul Aziz; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine Islam and secularism. This study uses a qualitative approach by applying descriptive methods and maudhu’i Interpretations. This type of qualitative approach is based on secondary data sources which are literature related to the topic of this research originating from journal articles, books, and others. Data analysis techniques are taken through the stages of inventory, classification, and interpretation. The technique of checking the validity of the data is carried out by means of library research. The research results obtained indicate that there are several findings that the author obtained including: the meaning of secularism, how to get the verse, as well as related discussions regarding secularism.